Comparative Study of Remimazolam and Midazolam During Sedated Upper Gastrointestinal Endoscopy: A Propensity Score Matching Analysis - Ryoji Ichijima; Hisatomo Ikehara; Tomomi Sugita; Daisuke Yamaguchi; Yasuhiko Nagata; Kanako Ogura; Mitsuru Esaki; Yosuke Minoda; Hiroyuki Ono; Yuki Maeda; Shinsuke Kiriyama; Tetsuya Sumiyoshi; et al. (JGH Open)
ABSTRACT Aim This study aimed to compare the use of remimazolam and midazolam in upper gastrointestinal endoscopy in Japan as a sub‐analysis of data from an investigator‐initiated clinical trial of remimazolam. Methods and Results Patients in two groups were matched using propensity score matching. We evaluated the time from the end of the gastrointestinal endoscopy until discharge, the time from the end of the procedure until awakening, and adverse events. Overall, 36 participants from the clinical trial population who underwent upper gastrointestinal endoscopy using remimazolam and 199 patients who underwent the procedure with midazolam during the same period were included in this study. Following propensity score matching, 34 patients in both groups were matched. The median time from the end of the procedure until awakening was 27.0 min (23.0–40.5 min) in the midazolam group (Group M) and 0 min (0–5.0 min) in the remimazolam group (Group R); the median time from the end of the upper gastrointestinal endoscopy until discharge was 39.0 min (35.0–52.5 min) in Group M and 5.0 min (0–5.0 min) in Group R (p < 0.01). Reported adverse events were hypotension and hypoxemia in one patient in Group R. Conclusion Compared with midazolam, remimazolam significantly shortened the time to patient awakening and duration until the patient could leave the endoscopy room. Trial Registration: The main study (REM‐IICT JP1) is registered with the Japan Registry of Clinical Trails: jRCT2031200360